Publication of studies registered in Clinical Trials Registry of India: An audit of mood disorder research protocols from 2009-2019 - Vikas Menon; Natarajan Varadharajan; Rini Joseph; Samir Kumar Praharaj; Chittaranjan Andrade (Indian Journal of Psychiatry)
Background: Selective publication of studies has important scientific, ethical, and public health implications. Aim: We studied selective publication among mood disorder research protocols registered in the Clinical Trials Registry of India (CTRI) database. We also examined the frequency and nature of protocol deviations among the published articles. Methods: Using a systematic search strategy, we examined the publication status of all mood disorder-related research protocols registered in the CTRI database from inception till December 31, 2019. Logistic regression analysis was used to identify variables associated with selective publication. Results: Of 129 eligible protocols identified, only a third (n = 43, 33.3%) were published in literature; among those published, only 28 (21.7%) were placed in MEDLINE indexed journals. Protocol deviations were observed in more than half of the published papers (n = 25, 58.1%); many of these (41.9%) were related to sample size deviations, though, importantly, deviations in primary and secondary outcomes were also noted (16.2%). Retrospective registration of trials (odds ratio, 2.98, 95% confidence interval, 1.32–6.71) was significantly associated with publication; other variables, such as funding status or multicentric sampling, were not associated with eventual publication. Conclusions: Two out of three mood disorder research protocols registered in India do not translate into published research. These findings from a low- and middle-income country with limited spending on health care research and development represent wastage of resources and raise scientific and ethical concerns about unpublished data and futile patient participation in research.